Pengadaan Sarana Prasarana di SMP Negeri 2 Rantau Alai Ogan Ilir - Hasbi, M.; Permatasari, Dian; Ibrahim, Ibrahim (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This research aims to discuss the procurement of facilities and infrastructure at SMP Negeri 2 Rantau Alai Ogan Ilir. This study uses a descriptive qualitative approach with a qualitative research type. The research method employed is a descriptive approach with data collection techniques through observation, interviews, and documentation. The data analysis techniques used include data reduction, data presentation, data verification, and conclusion drawing. The validity test of the research data utilizes source triangulation and technique triangulation. The results of the study indicate that the procurement of facilities and infrastructure at SMP Negeri 2 Rantau Alai Ogan Ilir has been carried out well. The research findings can be seen in the procurement process, which includes the identification of needs, budget planning, information gathering, procurement planning, tender or bidding opening, and bid evaluation. The author concludes that the procurement of facilities and infrastructure at SMP Negeri 2 Rantau Alai Ogan Ilir has been conducted effectively. This is evidenced by the identification of needs, budget planning, information gathering, procurement planning, tender or bidding opening, and bid evaluation